Implementasi Kepemimpinan Transformasional Kepala Sekolah Dalam Meningkatkan Prestasi Kepramukaan Di SDN Bringin 01 Kota Semarang - Arifana, Arifana; Bunyamin, Bunyamin; Rasiman, Rasiman (Cetta: Jurnal Ilmu Pendidikan, 2025)
In the field of education, school principals play a strategic role as leaders who motivate, inspire, and empower teachers and students to enhance the quality of education. Extracurricular activities, particularly scouting, significantly contribute to the improvement and development of students' character and behavior. Through scouting activities, students are not only trained in practical skills but also educated and instilled with values such as leadership, teamwork, and responsibility. SDN Bringin 01 in Semarang City is very optimistic and consistent in its commitment to developing scouting activities as part of the school's efforts to improve scouting achievements. However, the challenge lies in how the principal can effectively implement transformational leadership to enhance students' scouting achievements. This challenge is particularly relevant given the central role of the principal in creating a conducive environment for developing students' potential and interests. This research employs a qualitative approach using various techniques for data collection, including interviews, observations, and document analysis. By using this approach, the study aims to deeply explore the implementation of transformational leadership by the principal at SDN Bringin 01 in Semarang City in improving scouting achievements. The research seeks to examine the dynamics of a principal's leadership, including interactions between the principal and various stakeholders such as the school committee, teachers, scout trainers, and students. Additionally, this study will analyze how these interactions influence the success of scouting activities at the school. The results of this research indicate that the principal has successfully implemented transformational leadership principles effectively, including modeling behavior, motivation, effective communication, and wise decision-making. This leadership approach has proven to enhance teachers' motivation, dedication, collaboration, and competence in improving scouting achievements. Furthermore, there has been a significant increase in student participation in scouting activities, reflected in better achievements at both the sub-district and city levels.